Long-Term Safety and Efficacy of CT-Guided I125 Radioactive Seed Implantation as a Salvage Therapy for Recurrent Head and Neck Squamous Carcinoma: A Multicenter Retrospective Study - Jiang, Yuliang; Zhen, Peng; Dai, Jinchao; Li, Yixing; Liu, Shifeng; Xu, Junma; Wang, Yufeng; Tian, Suqing; Cui, Yue; Ji, Zhe; Guo, Fuxin; Qiu, Bin; et al. (Frontiers in Oncology, 2021)
Purpose To investigate the safety and efficacy of CT-guided I125 radioactive seed implantation (RSI) as a salvage therapy for recurrent head and neck squamous carcinoma (rHNSC) after external beam radiotherapy (EBRT) or surgery. Materials and Methods This is a multicenter retrospective study of 113 patients (83 males; median age 57 years) with rHNSC who underwent CT-guided I125 RSI between February 2003 and December 2017. Of the included patients, 107 patients previously received EBRT and 65 patients received surgery and all were ineligible or rejected for salvage surgery and/or repeat EBRT. Results During a median follow-up duration of 20 months (range, 3-152 months), 87 patients died. The 1-, 2-, 3-, and 5-year local control rate were 57.4%, 41.8%, 29.3%, and 15.2%, respectively. The median time to progression was 15 months [95% confidence interval (CI), 6.1-23.9 months]. The median overall survival (OS) was 20 months (95% CI, 12.4-27.6 months). The 1-, 2-, 3-, and 5-year OS rate were 63.6%, 44.6%, 29.9%, and 21.7%, respectively. Univariate and multivariate analyses revealed that KPS score and postoperative D90 were significantly associated with patients’ OS. The complications were mainly grade I/II skin and mucosal reactions: 18 cases (15.9%) of grade I/II and eight cases (7.0%) of grade III radiation dermatitis, and 14 cases (12.4%) of grade I/II and three cases (2.7%) grade III mucosal reactions. No grade IV or severer complications were found. Conclusion CT-guided I125 RSI may be safe as a salvage therapy for rHNSC after EBRT/surgery, yielding promising efficacy compared with historical data. KPS score and postoperative D90 may be significantly associated with OS.